The long-run weight of communism or the weight of long-run history? - Gérard Roland (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This study provides evidence that culture understood as values and beliefs moves very slowly. Despite massive institutional change, values and beliefs in transition countries have not changed much over the last 20 years. Evidence suggests that culture is affected by the long run historical past, in particular the participation in empires for over 100 years. Current institutional evolutions in transition countries might be more affected by their long run past than by the communist experience of the twentieth century.
Keywords: N10; O57; P20; P30; 330; culture; institutional change; transition; economic history